2019
DOI: 10.1021/acs.inorgchem.8b02433
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Lewis Acid-Mediated Capture and N–N Bond Cleavage of Hydrazine at Iron

Abstract: An iron complex bearing a pyridine(dicarbene) pincer was designed to probe the requirements of Lewis acid enabled N 2 H 4 capture and subsequent N-N bond cleavage. Appended boron Lewis acids were installed by two methods to circumvent the incompatibilities associated with Lewis acid/base quenching of free carbenes and boranes. N 2 H 4 capture by borane Lewis acids is dependent on both Lewis acidity and the steric profile about boron. A substitutionally inert primary coordination sphere at iron prevents an Fe-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 82 publications
1
23
0
2
Order By: Relevance
“…Exemplar of this notion, Szymczak and co-workers showed that iron could be coordinated to a pyridine(dicarbene) pincer ligand and subsequently hydroborated. 96 The scope of hydroboration was found to be modular using a series of monohydroboranes (HBR 2 ) where BR 2 = 9-BBN (9-borabicyclo[3.3.1]nonyl), Bsia 2 (sia = siamyl), BCy 2 (Cy = cyclohexyl), and BPin (Pin = pinacol). Exposure of the Bsia 2 -and BCy 2 -compounds, [( BR 2 CNC)Fe(CO) 2 ] to 1 equiv.…”
Section: Diboranyl Pincer Ligandsmentioning
confidence: 99%
“…Exemplar of this notion, Szymczak and co-workers showed that iron could be coordinated to a pyridine(dicarbene) pincer ligand and subsequently hydroborated. 96 The scope of hydroboration was found to be modular using a series of monohydroboranes (HBR 2 ) where BR 2 = 9-BBN (9-borabicyclo[3.3.1]nonyl), Bsia 2 (sia = siamyl), BCy 2 (Cy = cyclohexyl), and BPin (Pin = pinacol). Exposure of the Bsia 2 -and BCy 2 -compounds, [( BR 2 CNC)Fe(CO) 2 ] to 1 equiv.…”
Section: Diboranyl Pincer Ligandsmentioning
confidence: 99%
“…The differing reactivities for late-stage hydroboration by the set of complexes 1 , 3-PR 3 , and 4-R inform on the requirements for this process and provide a reasonable outline for making reaction predictions. Previously, our work with 1 demonstrated that, in the zerovalent state, both the N-heterocyclic carbenes and the carbonyl ligands were substitutionally inert . In contrast, divalent 2 was incompatible with hydroboration conditions, consistent with an increased lability of the N-heterocyclic carbene and/or acetonitrile ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Boron Lewis acids provide high steric and electronic tunability and can be incorporated into a metal–ligand construct through a variety of methods. While the addition of hydro- or haloboranes to metallacycles and diol/boronic acid condensation have been used to install boron groups postmetalation, hydroboration strategies offer the greatest ease, versatility, and generality (Figure , top). , The majority of reports using late-stage hydroboration strategies overcome the compatibility hurdles by using metals that form robust M–L bonds (limiting intramolecular Lewis pair formation), ancillary ligands that have low affinity for boron Lewis acids (limiting ligand abstraction), or metals that do not readily react with HBR 2 reagents (limiting metal-centered reactivity). , Examples that lack the above properties are rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Incorporation of hydrogen bond donor groups has been reported to support metal oxo and hydroxo ( A , Figure 1), 1a,1b,2 nitrite activation, 3 CO 2 reduction, 4 and other reactivity. 5 Ligands appended with Lewis acidic moieties have also been reported to promote hydrazine bonding at Fe, 6 reductive CO coupling ( B ), 7 selective alkyne hydrogenation, 8 and other small molecule activation. 9 Lewis base incorporation into the secondary coordination sphere of Fe complexes for N 2 reduction, 10 Ni catalysts for proton reduction ( C ), 11 and Co water oxidation catalysts 12 has reported to change catalyst selectivity and activity.…”
Section: Introductionmentioning
confidence: 99%